Determination of the Emission Inventory from Road Transport in the Tekkekoy (Samsun) District Center - Göksel Kaya (Doğal Afetler ve Çevre Dergisi)
Within the scope of this study, the emission amounts arising from vehicles cruising on the main highway in the Tekkekoy district center in Turkey, where the General Directorate of Highways counted vehicles in 2017, were calculated. The emission amounts were calculated using the emission factor, the number of vehicles and the length of the highway. The emission factors were selected suitably from the CORINAIR emission factor database in the form of velocity-related equations as vehicle class, type of fuel, emission standard and engine technology. The numbers of vehicles and route lengths were obtained from the data of the State Highways Traffic Volume Map published by the General Directorate of Highways of the Turkish Ministry of Transportation and Infrastructure. Emissions were calculated separately for 5 pollutants (CO, NOx, VOC, PM and SO2) by using the MATLAB programming language. Emission characteristics for each type of pollutant and for each type of vehicle (automobiles, light-duty commercial vehicles, buses and trucks) were identified depending on vehicle speeds. The results showed that the amounts of pollutants released to the atmosphere on the main highway where vehicle counts were made in the Tekkekoy district center in the year 2017 as 138.56 tons for CO, 150.23 tons for NOx, 18.33 tons for VOC, 5,01 tons for PM and 0.20 tons for SO2. Trucks had the highest share for the pollutants NOx and PM respectively as 66.36% and50,3%. Passenger cars had the highest share for the pollutants CO, VOC and SO2 respectively as 72.32%, 64.81% and 50%. The amounts of pollutant emissions were found to be at their minimum values in the speed range of 70–90 km/h.